2021
DOI: 10.1016/j.cyto.2021.155618
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 inflammatory endotype relates to low compliance, lung fibrosis, and severe complications in COVID-19

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 34 publications
(43 reference statements)
1
13
0
Order By: Relevance
“…SARS-CoV-2 infection can also precipitate macrophage activation syndrome, which is characterized by increased type II IFN-related responses as well as elevated IL-6, IL-1β, TNF-α, and ferritin levels [21]. Patients with severe COVID-19 typically have increased serum levels of IL-6, IL-8/CXCL8, CXCL9, CXCL10, TNF-α, MCP1/CCL2, RANTES/CCL5, IL-18, and MIP-1α/CCL3, which promote a sustained pro-inflammatory state that may persist for up to 60 days [22,23].…”
Section: Cytokine Responsesmentioning
confidence: 99%
“…SARS-CoV-2 infection can also precipitate macrophage activation syndrome, which is characterized by increased type II IFN-related responses as well as elevated IL-6, IL-1β, TNF-α, and ferritin levels [21]. Patients with severe COVID-19 typically have increased serum levels of IL-6, IL-8/CXCL8, CXCL9, CXCL10, TNF-α, MCP1/CCL2, RANTES/CCL5, IL-18, and MIP-1α/CCL3, which promote a sustained pro-inflammatory state that may persist for up to 60 days [22,23].…”
Section: Cytokine Responsesmentioning
confidence: 99%
“…Furthermore, a wealth of clinical data determines the positive correlation of heightened IL-18 concentrations with the occurrence of the ARDS, lung fibrosis, and AKI and disease severity, contributing to the early identification of critical COVID-19 patients [ 19 , 140 , 160 , 161 ] (Table 1 ). Concomitantly, some studies identified IL-18, alongside the IL-15 and Gal-9, as an organ-failure-specific immunological marker of the respiratory system [ 161 , 162 ].…”
Section: Il-18 and Covid-19mentioning
confidence: 99%
“…A study done by Singh et al showed sustained high levels of IL-18 consistent with CCR2, CX3CR1, and macrophage inflammatory factors even in the recovery stages of the infection, suggesting IL-18 s’ roles in the compromised immunity of recovered patients [ 173 ]. Likewise, in the recovery period from ARDS, the serum levels of IL-18, CCL3, and CXCL9 were higher in COVID-19 patients with dyspnea or renal failure, representing IL-18 as a reflecting marker of residual inflammation in these patients [ 161 ]. However, prediction analysis of cell-to-cell interactions utilizing data from the scRNA-Seq in a computational approach indicated that, in late recovery stage (LRS) patients, DC-derived IL-18 and TNF TNFSF13 accompanied by T cell-derived IL-2 and IL-4 might promote B cell survival, proliferation, and differentiation, culminating in the production of various SARS-CoV-2-specific Abs [ 83 ].…”
Section: Il-18 and Covid-19mentioning
confidence: 99%
“…To this regard, elevated MUC1 mucin protein levels were found in airway mucus of critical ill COVID-19 patients [191] as well as interleukins [164] , though no significant differences have been revealed in baseline levels of IL-1β, IL-6, and TNF-α between patients with COVID-19 and critically ill subjects with ARDS [192] . On the contrary, high levels of IL-18 were found in 85% of the COVID-19 patients that had ARDS and 78% of those that developed pulmonary fibrosis [193] . Further, levels of IL-13, one of the major factors implicated in lung fibrosis, have been demonstrated to be elevated in patients with severe COVID-19, underlining its ability in identifying COVID-19 patients who needed of mechanical ventilation [194] .…”
Section: What About the Lung Lesions In Post-covid-19 Patients?mentioning
confidence: 88%